Case-Based Learning for Enhancing Occupational Health Biomedical Literacy: Evidence from Exercise-Induced Oxidative Stress Education - Asih Luklu Susiati; Trinarti Senolangi; Andi Nadya Eka Putri; Sahari Bulan; Nur Amalia Alif (Al-Musannif, 2026)
Occupational fatigue and oxidative stress have become important concerns in Occupational Health and Safety (OHS) education due to their impact on workers’ physiological health and workplace performance. However, biomedical learning in OHS programs is often theoretical and lacks contextual learning experiences that promote scientific reasoning and biomedical literacy. This study aimed to investigate the effect of Case-Based Learning (CBL) on occupational health biomedical literacy among OHS students in the context of exercise-induced oxidative stress. A quasi-experimental pretest–posttest control group design was employed involving 42 undergraduate OHS students divided into an experimental group (n = 21) and a control group (n = 21). The experimental group received CBL instruction using authentic biomedical cases related to Malondialdehyde (MDA), Serum Glutamic Pyruvic Transaminase (SGPT), VO₂max, and occupational fatigue, while the control group received conventional lecture-based instruction. Data were collected using a biomedical literacy test assessing conceptual understanding, biomedical data interpretation, scientific reasoning, and occupational health decision-making. The results showed that the experimental group achieved a higher posttest score (84.52 ± 6.73) than the control group (71.38 ± 7.84). The normalized gain was also higher in the experimental group (0.65) than in the control group (0.35). Paired-samples t-test analysis revealed significant improvements in biomedical literacy scores in both groups (p < 0.001), with substantially greater gains observed in the CBL group. These findings indicate that integrating authentic biomedical cases through CBL effectively enhances biomedical literacy and scientific reasoning among OHS students and may serve as an effective strategy for contextual occupational health education.